Evaluation of methylene blue restaining versus conventional hydrogen peroxide decolorization in immunohistochemical diagnosis of melanoma - Weisong Wan; Le Wang; Yuye Zeng; Yuchang Hu; Yufei Liu (Scientific Reports)
Abstract This study seeks to address the challenge of melanoma identification in immunohistochemical (IHC) diagnosis, which is complicated by the similar coloration of melanin and DAB (Diaminobenzidine) staining, by introducing methylene blue counterstaining as an innovative solution. We compared the effectiveness of methylene blue counterstaining with that of the traditional hydrogen peroxide bleaching method in the diagnosis of melanoma. The study included 46 paraffin-embedded melanoma samples, and the staining efficacy for markers such as Melan A, HMB-45, PRAME, and Ki-67 was assessed via both methods. The results demonstrated that methylene blue counterstaining effectively converted the brownish-yellow melanin granules to a deep green color, significantly enhancing contrast and clarity with DAB staining. The average contrast and clarity scores for the methylene blue counterstaining method were 1.96 ± 0.21 and 1.91 ± 0.28, respectively, which were significantly greater than those of the conventional IHC group and the hydrogen peroxide bleaching group (P < 0.01). Furthermore, methylene blue counterstaining did not cause noticeable tissue damage or cellular morphology distortion, with tissue integrity scores comparable to those of the conventional IHC group (P > 0.05). Although the contrast and clarity also improved in the hydrogen peroxide bleaching group, it resulted in a significant decrease in tissue integrity (P < 0.01). This study is the first to apply methylene blue counterstaining in melanoma IHC analysis, demonstrating its advantages in enhancing staining quality, simplifying procedural workflows, and preserving antigenicity. This method provides a novel and effective tool for the pathological diagnosis of melanoma, potentially improving diagnostic accuracy and reliability.